The Difference of Length of Stay, Surgical Site Infection, Post Surgical Pain, and Bile Leak in Laparoscopic Cholecystectomy and Open Cholecystectomy - Dilla Putri; Santoso Jaeri; Agung Aji Prasetyo; Sigit Adi Prasetyo (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: The incidence of cholesistolithiasis is increased  due to the changes of diet to the western diet. The cholecystectomy is one of the treatments for cholecystolithiasis. It can be divided into laparoscopic cholecystectomy and laparotomy cholecystectomi. The previous study demonstrated that the laparoscopic cholecystectomy was better than laparotomy cholecystectomy for postoperative length of stay, surgical site infection, postoperative pain, and bile leak in cholecystolithiasis, but there is no official data  and research yet in Indonesia Objective: To determine the difference of  postoperative length of stay, surgical site infection, postoperative pain, and bile leak in laparoscopic cholecystectomy and laparotomy cholecystectomy.Methods: An analytic observational study with cross sectional design. Subject was patient who had undergone laparoscopic or laparotomy cholecystectomy from Dr Kariadi Hospital, Semarang and RSND Semarang during period of 2013 to 2019. The Mann Whitney-U test was used to determine the difference of length of stay as well the Chi Square test for determining the difference of surgical site infection, postoperative pain, and bile leak among both groups.Results: 34 (41.5%) men and 48 (58.5%) women with an age avarage of  49.84 ± 13.54 years were included. There were a significant difference between laparoscopic and laparotomy cholecystectomy in cholecystectolithiasis cases on postoperative hospital stay (p = 0.000), postoperative pain (p = 0.000), surgical site nfection (p = 0.000), and bile leak ( p = 0.013).Conclusion: Laparoscopic cholecystectomy was better than open cholecystectomy in postoperative hospital stay, surgical site infection, postoperative pain, and bile leak for cholecystolithiasis cases. Keywords: bile leak , cholecystetomy, cholecystolithiasis, laparoscopy, laparotomy